Effectiveness of Retraining as an Instrument for Solving the Problem of Structural Unemployment in the Czech Republic - Å tÃ¡fek, Pavel; Å Ã¡novÃ¡, Petra; NovotnÃ¡, Zuzana; LaputkovÃ¡, Adriana (International Journal of Economics and Financial Issues, 2016)
The aim of this paper is to evaluate effectiveness of retraining as an instrument for solving the problem of structural unemployment in the Czech Republic for the period of 2004-2011. Its partial aim is to determine indicators which assess retraining courses and to identify the degree of interdependence of individual parameters connected with retraining. The data were obtained from the Ministry of Labour and Social Affairs and from the Labour Office of the Czech Republic. Based on these, indicators of efficiency and effectiveness of retraining courses were established. Furthermore, statistically important dependencies which influence the expenditures on retraining, the number of participants and success rate of retraining were investigated. The results show a growing tendency for success of retraining courses. Using the proposed methodology, effectiveness of retraining courses was ascertained and the degree of interdependence of selected indicators was established. In conclusion, recommendations are formulated for stabilization of methodology for collection of relevant data to ensure more precise examination in the future. Keywords: retraining, active employment policy, effectiveness, unemployment, expenditures JEL Classifications: E23, M5, H5